DAMPAK KEBIJAKAN BBM BERSUBSIDI BAGI MASYARAKAT DI KELURAHAN OESAPA KECAMATAN KELAPA LIMA KOTA KUPANG - Vergilius Manehat; Veronika Ina Assa Boro; Frans Bapa Tokan (Journal Education and Government Wiyata, 2025)
This research is titled "The Impact of Subsidized Fuel Policy on the Community in Oesapa Village, Kelapa Lima Subdistrict, Kupang City." The problem formulation aims to describe and analyze the impact of both subsidized and non-subsidized fuel policies on the community in Oesapa Village, Kelapa Lima Subdistrict, Kupang City. The theory used to address the research problem is the policy theory. The primary data sources are informants, while secondary data consists of documents related to the research variables. Data collection techniques include interviews, observations, and documentation. The data analysis process involves data reduction, data presentation, conclusion drawing, and is then analyzed in a qualitative descriptive manner. The research findings indicate that: 1). Income Redistribution: This describes the income redistribution as the impact of the subsidized fuel policy on the community in Oesapa Village, represented by indicators such as Direct Cash Assistance (BLT) for poor communities, Wage Subsidy Assistance (BSU) for workers, and the Family Hope Program (PKH). 2). Procurement of Goods and Services: This describes the procurement of goods and services as the impact of the subsidized fuel policy on the community in Oesapa Village, represented by indicators such as the distribution of subsidized fuel to the poor. Based on the analysis above, the author concludes that the impact of the subsidized fuel policy, through income redistribution and the procurement of several types of goods and services, has a positive effect on the community in Oesapa Village, Kelapa Lima Subdistrict, Kupang City.